2018
DOI: 10.1002/cjas.1489
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Strategic Integration in Performance Improvement Through Purchasing Social Responsibility in Thailand

Abstract: This research aims to understand the performance of purchasing social responsibility (PSR) through moderating effect of purchasing strategic integration. The results show that PSR directly influences purchasing performance, while the relationship between PSR and purchasing performance is partially mediated by organizational learning. Moreover, strategic integration negatively moderates the relationship between PSR and purchasing performance. This study suggests that the adoption of PSR affects the operations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Jin et al (2019) revealed that sustainability orientation promotes innovation culture and helps building competitive advantage in R&D management. In addition, green initiative and sustainability orientation are reflected in shaping buyer-supplier management (Duangjan and Wang, 2019;Mehregan et al, 2014;Yang et al, 2020).…”
Section: Green Initiativementioning
confidence: 99%
“…Jin et al (2019) revealed that sustainability orientation promotes innovation culture and helps building competitive advantage in R&D management. In addition, green initiative and sustainability orientation are reflected in shaping buyer-supplier management (Duangjan and Wang, 2019;Mehregan et al, 2014;Yang et al, 2020).…”
Section: Green Initiativementioning
confidence: 99%
“…Jin et al (2019) revealed that sustainability orientation promotes innovation culture and helps building competitive advantage in R&D management. In addition, green initiative and sustainability orientation are reflected in shaping buyer-supplier management (Duangjan and Wang, 2019;Mehregan et al, 2014;Yang et al, 2020).…”
Section: Green Initiativementioning
confidence: 99%